A dispersion‐free multi‐access RF dissemination link with phase jitter compensation. Issue 1 (31st December 2020) - Zhu, Xiang; Jin, Tao; Fu, Ying; Chi, Hao; Liu, Weimin; Wang, Qihang; Feng, Pengyu
Abstract: A dispersion‐free scheme for stable multi‐access radio frequency dissemination in a fibre loop link is proposed and demonstrated. The phase jitter and dispersion‐induced power fading are suppressed simultaneously by transmitting different single‐band signals in opposite propagating directions. Experimentally, a 2.5 GHz radio frequency signal is steadily transmitted to different remote sites, with phase deviations less than 0.6 ps over 15, 000 s.